2020
DOI: 10.2478/pcssr-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

Motivation for Participation in Sports Based on Athletes in Team and Individual Sports

Abstract: There are many reasons why individuals are motivated to participate in sports. For athletes to participate in and keep up exercise, investigating the participation motivation of athletes is necessary. The aim of this study was to compare sport participation motivation of athletes in team and individual disciplines. The sample consisted of 265 athletes including four teams from football, volleyball, basketball, and handball and two individual disciplines of kung fu and taekwondo which were randomly selected. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 14 publications
5
18
1
1
Order By: Relevance
“…Just as there are differences between dropout reasons between genders, the results obtained conclude, like other studies [ 33 , 91 , 92 ], differences in the number and dropout reasons between individual and collective sports. These differences can be the result of different situations (attribution of success or failure, inadequate equipment environment, perception of enjoyment, sports level, etc.)…”
Section: Discussionsupporting
confidence: 86%
“…Just as there are differences between dropout reasons between genders, the results obtained conclude, like other studies [ 33 , 91 , 92 ], differences in the number and dropout reasons between individual and collective sports. These differences can be the result of different situations (attribution of success or failure, inadequate equipment environment, perception of enjoyment, sports level, etc.)…”
Section: Discussionsupporting
confidence: 86%
“…However, no studies have been found that evaluate the motivation of the population during this pandemic period, the psychological aspects being especially relevant since previous studies during periods of confinement have shown the existence of negative impacts, such as increased stress and depression caused by social distancing [ 27 ]. Previous studies have indicated that no differences have been observed between the motivations of sportspersons and exercisers, or between individual and team sports athletes [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results correspond to existing data indicating that the dominant factor influencing the decision of youngsters to join competitive sport is intrinsic (Knight & Holt, 2011;Ryan & Deci, 2000a, b;Weinberg & Gould, 2015). In addition, most of the studies focused on young males and the few studies which compared the genders indicated inconsistent results (e.g., Gonçalves et al, 2007;Moradi et al, 2020). Results of previous studies emphasized the importance of intrinsic motivation, focusing on "fun", while data of the current study emphasized reasons relating to the personal will of the young girls (e.g., "I want") and the need to win.…”
Section: Discussionmentioning
confidence: 55%
“…For example, one study found that girls participate in sport more for internal rather than external motives (e.g., fun, being with friends) compared to boys (Chantel et al, 1996;Wang & Liu, 2007). In another study, gender motivations were compared in team sports versus individual sports, and it was found that female athletes had higher overall motivation to participate in sports than male athletes (Moradi et al, 2020). Another finding in the context of gender comparisons in team sports (i.e., football and volleyball) showed that girls and boys attached importance to the same three motives for participating ("technical ability", "competition" and "group activity") but differed in the level of importance of each factor (Vignadelli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%